Cultural Wealth, Co-creation, and Conversations: Reimagining Academic Internships - Tinajero-Vazquez, Karen; Carr, Allison (Canadian Journal of Academic Librarianship / Revue canadienne de bibliothéconomie universitaire, 2024)
In this article, two librarians reflect on their experience as an intern and supervisor navigating traditional and antiquated norms upheld in academia. The intern, a first-generation Mexican-American student, describes the shift in her values, beliefs, and identity as she confronts the extractive practices embedded in internships, resulting in a collaborative and critical internship. The internship supervisor, a senior librarian, also reflects on her role in resisting these exploitative dynamics by using the community cultural wealth model, which recognizes the knowledge students of colour bring from their homes and communities. The intern and supervisor introduce ideas for improving the internship experience by embracing community cultural wealth, critiquing the role of neoliberal multiculturalism, and addressing the systemic extraction that hinders the professional development of marginalized students.